Multidisciplinary, three-dimensional and individualized comprehensive treatment for severe/critical COVID-19 (2020)
Severe/critical cases account for 18%–20% of all COVID-19 patients, but their mortality rate can be up to 61.5%. Furthermore, all deceased patients were severe/critical cases. The main reasons for the high mortality of severe/critical patients are advanced age (>60 years old) and combined underlying diseases. Elderly patients with comorbidities show decreased organ function and low compensation for damage such as hypoxia and inflammation, which accelerates disease progression.The lung is the main target organ attacked by SARS-CoV-2while immune organs, liver, blood vessels and other organs are damaged to varying degrees. Livervolume is increased, and mild active inflammation and focal necrosis are observed in the portal area.Virus particles have also been detectedin liver cells. Therefore, multidisciplinary teams (MDT) and individualized treatment plans, accurate prediction of disease progression and timely interventions are vital to effectively reduce mortality. Specifically, a “multidisciplinary three-dimensional management, individualized comprehensive plan” should be implemented. The treatment plan complies with three principles, namely, multidisciplinary management of patients, individualized diagnosis and treatment plans, and timely monitoring and intervention of disease. MDT members are mainly physicians from critical medicine, infection and respiratory disciplines, but also include cardiovascular, kidney, endocrine, digestion, nerve, nutrition, rehabilitation, psychology and specialty care. According to a patient’s specific disease condition, an individualized diagnosis and treatment plan is formulated (one plan for one patient). While selecting individualized antiviral, anti-inflammatory and immunomodulatory treatment, we also strengthen nutritional support, psychological intervention, comprehensive rehabilitation and timely and full-course intervention to develop overall and special nursing plans. In response to the rapid progression of severe/critical patients, MDT members need to establish a three-dimensional management model with close observation and timely evaluation. The MDT should make rounds of the quarantine wards both morning and night, and of critical patient wards nightly, to implement “round-the-clock rounds management”, to accurately predict disease progression, perform quick intervention and prevent rapid deterioration of the patient. Our MDT has cumulatively treated 77 severe/critical COVID-19 cases, including 62 severe cases (62/77, 80.5%) and 15 critical cases (15/77, 19.5%), with an average age of 63.8 years. Fifty-three cases presented with more than one underlying disease (53/77, 68.8%) and 65 severe cases recovered from COVID-19. The average hospital stay of severe/critical cases was 22 days, and the mortality rate was 2.6% (2/77), both of which were significantly lower than the 30–40 days and 49.0%–61.5%, respectively, reported in the literature. Therefore, a multidisciplinary, three-dimensional and individualized comprehensive treatment plan can effectively reduce the mortality rate of severe/critical COVID-19 and improve the cure